Complement as a vital nexus of the pathobiological connectome for acute respiratory distress syndrome: An emerging therapeutic target - Yang, Zhangsheng; Nicholson, Susannah E.; Cancio, Tomas S.; Cancio, Leopoldo C.; Li, Yansong (Frontiers in Immunology, 2023)
The hallmark of acute respiratory distress syndrome (ARDS) pathobiology is unchecked inflammation-driven diffuse alveolar damage and alveolar-capillary barrier dysfunction. Currently, therapeutic interventions for ARDS remain largely limited to pulmonary-supportive strategies, and there is an unmet demand for pharmacologic therapies targeting the underlying pathology of ARDS in patients suffering from the illness. The complement cascade (ComC) plays an integral role in the regulation of both innate and adaptive immune responses. ComC activation can prime an overzealous cytokine storm and tissue/organ damage. The ARDS and acute lung injury (ALI) have an established relationship with early maladaptive ComC activation. In this review, we have collected evidence from the current studies linking ALI/ARDS with ComC dysregulation, focusing on elucidating the new emerging roles of the extracellular (canonical) and intracellular (non-canonical or complosome), ComC (complementome) in ALI/ARDS pathobiology, and highlighting complementome as a vital nexus of the pathobiological connectome for ALI/ARDS via its crosstalking with other systems of the immunome, DAMPome, PAMPome, coagulome, metabolome, and microbiome. We have also discussed the diagnostic/therapeutic potential and future direction of ALI/ARDS care with the ultimate goal of better defining mechanistic subtypes (endotypes and theratypes) through new methodologies in order to facilitate a more precise and effective complement-targeted therapy for treating these comorbidities. This information leads to support for a therapeutic anti-inflammatory strategy by targeting the ComC, where the arsenal of clinical-stage complement-specific drugs is available, especially for patients with ALI/ARDS due to COVID-19.